Respuesta :

ImKC

Answer: x = 7  and  y = 2

Step-by-step explanation:

Since x is already defined for us, we can substitute for it in the second equation which gives us:

(5y - 3) + y = 9

6y - 3 = 9

6y = 12

y = 2

Then find x using y

x = 5(2) - 3

x = 10 - 3

x = 7

Answer:

Step-by-step explanation:

x = 5y - 3  and  x + y = 9

solve to get y

5y - 3 = x  and  y = 9 - x

    5y = x + 3

      y = x/5 + 3/5

     y = x+3/5

substitute y=9-x into y=x/5+3/5

   9 - x = x+3/5

 5(9-x) = x + 3

45 - 5x = x+3

 -5x -x = 3 - 45

     -6x = -42

        x = 7